Tingkat Pemahaman Mahasiswa dan Peran Tax Center (Studi Kasus Universitas Terbuka) - Syafiqoh Nurhayati; Jasrial; Dedy Juniadi; Ridha Azka Raga; Husna Putri Pertiwi; Jufri Yandes (Universitas Terbuka, 2022)
Tax Center (TC) in Higher Education becomes the third party between the Directorate General of Taxes and the Community (Taxpayers) in carrying out their tax obligations. The number of universities that have Tax Centers in Indonesia is only 10.7% of the total 3,119 universities in Indonesia. This indicates that awareness of the existence of TC is still unknown, universities must synergize with students because they are the successors of the nation which opens people's eyes to the importance of the role of taxes for development in Indonesia. This research examines the level of understanding of students and the role of the Tax Center at the Universitas Terbuka, the method used is mixed methods. The sample used convenience sampling in distributing questionnaires to students whose results were 67.92% which was not good about the existence of TC UT. Its role has been carried out is only 25%, namely: collaboration with third parties, and the Tax Center is open to all disciplines. This needs to be optimized because when partners are ready to help, then how do we synergize with students. After that, an interview was conducted with the person in charge of the Tax Center at the Distance Learning Program Unit-UT Surabaya (UPBBJ-UT) whose result was that the Tax Center had to be vacuumed due to limited Human Resources in managing the Tax Center and workload for each employee there was aggravated by the pandemic. The result of this study is that the role of the Tax Center is far from being well understood by students, so an FGD was carried out with the Universitas Gunadarma Tax Center as a reference for a better UT TC in the future. As a result, we need the support of the leadership (Rector) because TC can be a potential core business and is structurally recommended to become a unit under the Rector.